The Practical Way of Generosity (Dana) to Achieve Real Happiness in Theravada Buddhism - Thukhavati, Thukhavati (Journal of International Buddhist Studies, 2023)
This qualitative research aims to analysis the Theravāda Buddhist ways of practice of generosity (dāna) to achieve real happiness of life in contemporary society. It consists of three objectives, namely: (1) to study the concept, types and practice of generosity (dāna) in Buddhist scriptures, (2) to study the components of dhamma practice to achieve real happiness of life in contemporary society and (3) present the Theravāda Buddhist practical ways of generosity (dāna) to achieve real happiness of life in contemporary society. This research methodology was a kind of qualitative research. In this research, the researcher presents benefits and obstructions according to modern ways and Pāḷi suttas and, and how to practice the generosity to achieve real happiness of life in contemporary society according to Theravāda Buddhist doctrines in Pāḷi canon. There are many Theravāda Buddhist practical ways of generosity (dāna) to achieve real happiness of life: the practice of generosity with social ethics, volition (cetanā), faith (saddhā), loving-kindness (mettā), compassion (karuṇā) and morality (sīla).